Odnos navezanosti med očetom in otrokom v obdobju zgodnjega otroštva - Brajović, Tajana (Psihološka obzorja (Ljubljana), 2007)
Internalized working model of attachment, which affects quality of interactions with others, can remain relatively stable throughout a person's life. Attachment relationship seems to have some universal characteristics regardless of the form of the relationship (romantic partners relationship or parent-infant relationship). We were trying to develop a questionnaire of the attachment relationship between a father and his child in early childhood, that could offer comparable results and would be relatively easy to answer and validate. The questionnaire presented in this paper was adapted from the Experiences in Close Relationships - Revised (ECR-R; Fraley, Waller and Brennan, 2000) with regard to the relationship between a father and a child. This adapted inventory is a self-report questionnaire for fathers and is used for establishing father's perceptions of anxiety and avoidance in the attachment relationship with his child in early childhood. Analysis of 32 statements adapted from the ECR-R proved a 22 item form of the questionnaire (12 items on the anxiety and 10 items on the avoidance subscale) to be adequate. Principal component analysis of 22 items showed a two-component solution. Reliability of both subscales of the adapted instrument for 22 item solution proved to be acceptably high. In the future, criteria validity of the adapted instrument should be tested and some changes in the content of the existing items as well as some of the excluded items should be considered, and the revised version of the adapted ECR-R should be aplied to the representative sample of fathers. A version of the adapted ECR-R for mothers of children could also be formed.
Keywords: navezanost; attachment theory; očetje; otroci; child; otroštvo; medosebni odnosi; psihologija; psychology